A test of inference by exclusion in grey parrots (Psittacus erithacus): Replication of a parrot-child comparative study using additional avian subjects - Pepperberg, Irene M; Hartsfield, Leigh Ann (Journal of comparative psychology (Washington, D.C. : 1983), 2025)
Grey parrots have been shown to reason via inference by exclusion in various experiments, but so far only one bird has been shown to succeed on a four-cup task originally tested on young children, a purportedly stronger test of inference than experiments involving two cups. In the procedure with four cups (two pairs: AB, CD), a reward is hidden in one cup of each pair-for example, B, C; then one cup-for example, A-is shown to be empty. Successful subjects should conclude that the reward is 100% likely in B, only 50% likely in C or D, and accordingly choose B, thereby demonstrating modal and logical concepts in addition to epistemic ones. Here we replicate the task with three other Grey parrots to demonstrate that the ability is not restricted to one individual with extensive experimental experience. Thus, several subjects are now available for further testing necessary to examine the extent to which Grey parrots understand inference by exclusion. (PsycInfo Database Record (c) 2025 APA, all rights reserved).